Luminescence behavior of CsI:Ag thin films. (May 2020) - Khurana, Rashmeet Kaur; Singh, Inderpreet; Kumar, Kuldeep; Arun, P.; Madhwal, Devinder
Abstract: Thin films of Cesium iodide with silver doping in ratio of 500:1, 400:1 and 200:1 were grown by thermal evaporation. The structural, compositional and photoluminescence behavior of these films were studied. It was found that depending on the doping concentration, silver atoms either took up interstitial positions or displaced the cesium atom from the lattice. Based on whether silver existed in interstitial positions (low Ag doping) or had made substitutional doping (high Ag doping), various photoluminescence emission peaks appeared. The interplay of these emissions give an insight to the nature of CsI:Ag thin films and their potential use as a scintillator. The variation of film thickness for 200:1 doping was also studied to compare the changes in PL emission.